â€œANALISIS PENILAIAN KINERJA PERUSAHAAN DENGAN TINGKAT PROFITABILITAS DAN SOLVABILITAS PADA PERUSAHAAN PERSEROAN (PERSERO) PT TELEKOMUNIKASI INDONESIA, TBKâ€ - B51110037, Leo Jendi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
This research aims to know the performance of PT Telekomunikasi Indonesia , Tbk with the level of profitability and solvency . Proftabilitas ratio used in this study is the ratio of net profit margin , return on assets , return on equity . And Solvency ratios used in this study is the ratio of debt-to- equity ratio , Debt Ratio , Times Interest Earned . PT Telekomunikasi Indonesia , Tbk is a state-owned enterprises engaged in the field of Telecommunication , Telkom Fundamentals strong with good performance also ultimately reflected in the performance of the Company's shares of PT Telekomunikasi Indonesia , Tbk . This study used a descriptive method that is in the form of case studies . Collecting data by reading and studying the data obtained through documents or reports of activities of the company in accordance with the research topics that are downloaded from the internet . These results indicate that the performance of PT Telekomunikasi Indonesia , Tbk still not reached the ideal and need to improve in terms of regulating operating expenses and increase innovation that exist in PT Telekomunikasi Indonesia , Tbk . Keywords : Profitability and Solvency Ratio